Financial Institution and Public Listed Companies: How the Supervision Regulated Under the Indonesian Law? - Suwinto Johan (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
This study aims to analyze the supervision process and regulations of directors in managing a company, especially in financial institutions and public listed companies under the Indonesia law. This study uses normative juridical method with statute and conceptual approach. The primary legal material obtained from Law Number 8 of 1995 on Capital Market (UU Pasar Modal), Law Number 40 of 2007 on Limited Liability Company (UU PT), Law Number 21 of 2011 on Financial Services Authority (UU OJK), Financial Services Authority Regulation (POJK) Number 3/POJK.05/2013, POJK Number 11/POJK.05/2014, POJK Number 33/POJK.04/2014, POJK Number 1/POJK.05/2015, POJK Number 55/POJK.04/2015, POJK Number 27/POJK.03/2016, POJK Number 35/POJK.05/2018. The secondary legal material used in this study including books, journals and other documents related to the topic. This study concludes that the current laws and regulations are quite enough in regulating the supervision of parties, from general statutory regulations to the regulations of the relevant authorities. Otherwise, the Indonesian government need to amend the regulation mentioned especially the provision related to the penal sanctions to the directors and company parties.